Broad tunable photonic microwave generation based on period-one dynamics of optical injection vertical-cavity surface-emitting lasers - Ji, Songkun; Hong, Yanhua; Spencer, Paul S.; Benedikt, Johannes; Davies, Iwan (Optics express, 2017)
Photonic microwave generation based on period-one dynamics of an optically injected VCSEL has been study experimentally. The results have shown that the frequency of the generated microwave signal can be broadly tunable through the adjustment of the injection power and the frequency detuning. Strong optical injection power and higher frequency detuning are favorable for obtaining a high frequency microwave signal. These results are similar to those found in systems based on distributed feedback lasers and quantum dot lasers. The variation of the microwave power at the fundamental frequency and the second-harmonic distortion have also been characterized.